Transformasi Digital dan Emisi Karbon: Analisis Bibliometrik atas Perkembangan Riset Global - Sifa Rhodatul Jannah Subagio; Andri Prastiwi (SAFE-Network, 2026)
This study aims to map the development, publication trends, and intellectual structure of the literature on digital transformation and carbon emissions in the context of corporate sustainability. The method used is a bibliometric analysis of scientific publications indexed in the Scopus database. Data collection was conducted through a keyword-based search strategy with restrictions on the field of study, document type, and language, resulting in 165 documents analyzed. The results indicate a significant increase in the number of publications since 2021, suggesting growing academic attention to the role of digital transformation in the management and reporting of carbon emissions, as well as efforts to support corporate sustainability. Additionally, the analysis revealed that digital transformation is increasingly viewed as a strategic factor in enhancing the transparency and accountability of information related to carbon emissions. Theoretically, this study enriches the literature on the relationship between digital transformation and carbon performance and opens opportunities for the development of research models, particularly in the context of developing countries. Practically, these findings provide a comprehensive overview for researchers and research institutions in identifying future research directions, trends, and opportunities. The novelty of this study lies in the bibliometric approach used to systematically map the relationship between digital transformation and carbon emissions management.